The Study of the Gaṇḍavyūha sūtra: A Recent Publication - Silk, Jonathan A. (Indo-Iranian journal, 2026)
The publication of a Sanskrit-Tibetan-Chinese Index to the Gaṇḍavyūha sūtra offers the opportunity to consider some of the problems and challenges in the study of this influential Mahāyāna sūtra.